Pengaruh Konflik Peran Terhadap Kinerja Auditor Dengan Stres Kerja Sebagai Variabel Mediasi - Lismawati Lismawati; Fenny Marietza; Citra Yuliana (UNIVED Press, 2022)
The objective of this study is to analyze the influence of role conflict on auditor performance and analyse the mediating role of job stress on influence of role conflict toward auditor performance. Research respondents were 52 auditors in the Province Inspectorate Office. This research is a survey research to identify and describe phenomena according to conditions in the field. As a means of collecting data with a questionnaire, then the data obtained is discussed and described systematically in order to obtain conclusions. The data analysis method used is descriptive analysis and partial least square. The results showed that: role conflict has a negative effect on the performance of auditor, role conflict has a positive effect on the job stress of auditor, this result means that the higher the role conflict, the higher the auditor's job stress, job stress has a negative effect on the performance of auditors, job stress has a mediating role on the effect of role conflict on auditor performance. The mediating role of job stress is partially mediation, meaning that the direct influence of role conflict on auditor performance can still occur, even without being mediated by job stress.